Rikkunshito, a Kampo Medicine, Ameliorates Post-operative Ileus by Anti-inflammatory Action - Mari Endo; Masatoshi Hori; Hiroshi Ozaki; Tetsuro Oikawa; Toshihiko Hanawa (Elsevier, 2014)
Rikkunshito (RKT), a Kampo (Japanese herbal) medicine, is used as a prokinetic for patients with various diseases including functional dyspepsia. RKT promotes delayed gastric emptying via 5-HT3 receptor blockade. Otherwise, RKT increases ghrelin release via 5-HT2B and 5-HT2C receptor activation. Recent studies revealed that ghrelin and 5-HT3 receptor antagonists have an anti-inflammatory effect. So we hypothesize that RKT may have an anti-inflammatory action in the post-operative ileus. Intestinal manipulation (IM) was applied to the distal ileum of mice. RKT was administered orally 4 times before and after IM. Gastrointestinal transit in vivo, leukocyte infiltration, and gastric emptying were analyzed. We also investigated the effects of the 5-HT3 receptor agonist m-chlorophenylbiguamide (mCPBG) and ghrelin-receptor antagonist [d-Lys3]-GHRP-6 on the ameliorative action of RKT. RKT treatment led to recovery of the delayed intestinal transit and gastric emptying rate induced by IM. RKT significantly inhibited the infiltration of neutrophils and macrophages. [d-Lys3]-GHRP-6 reduced and mCPBG partially reduced the RKT-mediated anti-inflammatory activity, as monitored by infiltrating macrophages and neutrophils. RKT serves as a novel therapeutic agent for POI characterized by its anti-inflammatory potency, in addition to prokinetic action. The RKT-induced anti-inflammatory activity may be partly mediated by inhibition of the 5-HT3 receptor and ghrelin release. Keywords:: anti-inflammatory action, rikkunshito, postoperative ileus, ghrelin, 5-HT3